Exploration Strategies of Coordinated Multi-Robot System: A Comparative Study - Ayman. El shenawy; Khalil. Mohamed; Hany. M. Harb (IAES International Journal of Robotics and Automation (IJRA), 2018)
Environment Exploration is the basic process that most of Multi Robot Systems applications depend on it. The exploration process performance depends on the coordination strategy between the robots participating in the team.  In this paper the coordination of Multi Robot Systems in the exploration process is surveyed, and the performance of different Multi Robot Systems exploration strategies is contrasted and analyzed for different environments and different team sizes.